PENGARUH IDEALISME, RELATIVISME, PENGETAHUAN, GENDER DAN UMUR PADA PERILAKU TIDAK ETIS AKUNTAN - Damayanthi, Putu Dewi Adi; Juliarsa, Gede (E-Jurnal Akuntansi, 2016)
Ethical behavior is the behavior of someone who can act according to the rules, laws and morals that have been set out in a professional field. Some scandals that occurred in the accounting profession pose different perceptions of prospective accountants are students. The purpose of this study is to determine the effect idelisme, relativism, the level of knowledge, gender and age on unethical behavior accountant. The sample was 120 students S1 Faculty of Economics and Business, University of Udayana who have taken courses Auditing 1. The data was collected through questionnaire deployment with purposive sampling technique. The results showed that the idealism and the level of knowledge has a negative effect, relativism are positive effect, as well as gender and age had no effect on unethical behavior accountant.
Keywords: idealism, relativism, knowledge, age, gender, perception